Improving students' mathematical problem-solving ability through the think pair share cooperative learning model: A study of the quantitative experimental - Mursalin, M; Saputra, Eri (SAINTIS Publishing, 2023)
This study aims to see the improvement of students' mathematical problem solving ability through the application of Think Pair Share type cooperative learning model. Mathematical problem solving is the ability to identify the elements known, asked, and the sufficiency of the elements needed, able to make or compile mathematical models, can choose and develop solution strategies, able to explain and re-examine the answers obtained. This research uses a quantitative approach with a quasi experimental design and a nonequivalent control group design. The sample selection technique is using purposive sampling technique. The population in this study were all students of SMP Negeri 1 Juli class, while the samples were two classes, namely class VII2 as the experimental class and class VII3 as the control class. The data collection technique in this study used a mathematical problem-solving ability test. Data analysis carried out for the mathematical problem-solving ability test using non-parametric tests because the data is not normally distributed, the data is processed using SPSS 18 software and the results of non-parametric tests obtained a significant value of 0.000 significant level α = 0.05 then according to the hypothesis criteria If the significance value 0.05 then H0 is rejected and Ha is accepted. So, it can be concluded that the mathematical problem-solving ability of students who get the application of the Think Pair Share type cooperative learning model is better than students who get the scientific learning model.